Perfect Timing - Anderson, Catherine (Adeline Catherine); Copyright Paperback Collection (Library of Congress) (New York : Signet, 2013)
When a mysterious woman named Ceara shows up at his house, insisting that his dying sister-in-law can be cured if he marries her, Quincy Harrigan agrees despite his doubts, only to discover that she is a time-traveling druid.
Keywords: Druids and druidism -- Fiction; Time travel -- Fiction; Man-woman relationships -- Fiction; Love stories; Fantasy fiction